Differential Disrupting Effects of Prolonged Low-Dose Exposure to Dichlorodiphenyltrichloroethane on Androgen and Estrogen Production in Males - Yaglova, Nataliya V. (Int J Mol Sci, 2021)
Dichlorodiphenyltrichloroethane (DDT) is the most widespread, persistent pollutant and endocrine disruptor on the planet. Although DDT has been found to block androgen receptors, the effects of its low-dose exposure in different periods of ontogeny on the male reproductive system remain unclear. We evaluate sex steroid hormone production in the pubertal period and after maturation in male Wistar rats exposed to low doses of o,p’-DDT, either during prenatal and postnatal development or postnatal development alone. Prenatally and postnatally exposed rats exhibit lower testosterone production and increased estradiol and estriol serum levels after maturation, associated with the delayed growth of gonads. Postnatally exposed rats demonstrate accelerated growth of gonads and higher testosterone production in the pubertal period. In contrast to the previous group, they do not present raised estradiol production. All of the exposed animals exhibit a reduced conversion of progesterone to 17OH-progesterone after sexual maturation, which indicates putative attenuation of sex steroid production. Thus, the study reveals age-dependent outcomes of low-dose exposure to DDT. Prenatal onset of exposure results in the later onset of androgen production and the enhanced conversion of androgens to estrogens after puberty, while postnatal exposure induces the earlier onset of androgen secretion.